HUBUNGAN MODEL, PENDEKATAN, DAN STRATEGI PEMBELAJARAN DENGAN TEORI BELAJAR KONSTRUKTIVISME DAN HUMANISME DI SD/MI - Imel Lisanti (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
This article aims to examine the relationship between learning models, approaches, and strategies and the theories of constructivism and humanism in elementary schools (SD/MI). In basic education practice, the selection of appropriate learning models, approaches, and strategies greatly determines the success of the teaching and learning process. Constructivist theory emphasizes that students construct their own knowledge through experience and interaction with their environment, while humanistic theory views learners as whole individuals whose potentials, interests, and needs must be respected and optimally developed. Through a literature review approach, this article analyzes the conceptual relationship between learning models such as problem-based learning, cooperative learning, and contextual learning and the principles of constructivism. In addition, it explains how student-centered approaches and strategies align with humanistic values, including respect for individual differences, the development of intrinsic motivation, and meaningful learning. The findings indicate that learning models, approaches,and strategies systematically designed based on constructivist and humanistic theories can create active, participatory, and enjoyable learning experiences, while supporting students’ cognitive, affective, and psychomotor development in elementary schools (SD/MI). Therefore, the integration of these two learning theories serves as an essential foundation for designing effective learning that promotes the holistic development of learners.